The Future of AI in Governance: Building Self-Adapting GRC Systems - Naresh Kumar Methuku (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The potential of artificial intelligence to revolutionize the creation of self-adapting Governance, Risk, and Compliance (GRC) systems is explored in this article. It discusses how organizations are transitioning from traditional, manual GRC processes to sophisticated AI-driven solutions that can autonomously adapt to evolving regulatory landscapes. The article illustrates how reinforcement learning, adaptive algorithms, and neural networks reshape GRC practices by examining current implementation challenges, technological foundations, and future opportunities. It also discusses critical implementation factors across technological, regulatory, and organizational aspects while highlighting real-world applications in intelligent policymaking, predictive risk management, and ongoing compliance monitoring. The article addresses future developments in GRC technology, such as enhanced ecosystem creation, advanced analytics, and integration capabilities. Analyzing prospects and challenges provides valuable insights for companies implementing self-adapting GRC systems while maintaining robust governance frameworks.